Controlled Release of the α-Tocopherol-Derived Metabolite α-13′-Carboxychromanol from Bacterial Nanocellulose Wound Cover Improves Wound Healing - Jessica Hoff; Berit Karl; Jana Gerstmeier; Uwe Beekmann; Lisa Schmölz; Friedemann Börner; Dana Kralisch; Michael Bauer; Oliver Werz; Dagmar Fischer; Stefan Lorkowski; Adrian T. Press (Nanomaterials, 2021)
Inflammation is a hallmark of tissue remodeling during wound healing. The inflammatory response to wounds is tightly controlled and well-coordinated; dysregulation compromises wound healing and causes persistent inflammation. Topical application of natural anti-inflammatory products may improve wound healing, in particular under chronic pathological conditions. The long-chain metabolites of vitamin E (LCM) are bioactive molecules that mediate cellular effects via oxidative stress signaling as well as anti-inflammatory pathways. However, the effect of LCM on wound healing has not been investigated. We administered the α-tocopherol-derived LCMs α-13′-hydroxychromanol (α-13′-OH) and α-13′-carboxychromanol (α-13′-COOH) as well as the natural product garcinoic acid, a δ-tocotrienol derivative, in different pharmaceutical formulations directly to wounds using a splinted wound mouse model to investigate their effects on the wounds’ proinflammatory microenvironment and wound healing. Garcinoic acid and, in particular, α-13′-COOH accelerated wound healing and quality of the newly formed tissue. We next loaded bacterial nanocellulose (BNC), a valuable nanomaterial used as a wound dressing with high potential for drug delivery, with α-13′-COOH. The controlled release of α-13′-COOH using BNC promoted wound healing and wound closure, mainly when a diabetic condition was induced before the injury. This study highlights the potential of α-13′-COOH combined with BNC as a potential active wound dressing for the advanced therapy of skin injuries.